Social Bioclimatic Urban House Prototype in Arid Area Energy and Economic Assessment - Kurban, Alejandra Silvia (2017)
The energetic and economic evaluation of an evolutionary bioclimatic social house prototype designed in the research unit, for urban arid zones, is presented, calculating their respective costs. The performance of passive systems is evaluated with the Optimix Program, using the Collector Load Rate Method (Los Álamos National Laboratory). The investment alternatives are adopted from the calculation from the Net Present and Marginal Value. The results quantify the use of passive solar systems to make more efficient the thermal and economic benefits of the executed prototypes. The winter thermal load, to which the homes are exposed, is reduced by 64.1%, with technics of energy conservation and the improvement of solar systems and variants applied. Energy savings result in 20% and 22% and the amortization of 2.4 years and 2.3 years, depending on the orientation of the prototype (azimuth 0° N and ± 15° N respectively.